Child soldiers and disability: gaps in knowledge and opportunities for change. Issue 3 (3rd May 2016) - Johnson, Dustin; Whitman, Shelly
Abstract: The recruitment and use of child soldiers are a pressing peace and security issue around the world. The United Nations currently lists 7 government militaries and 52 non-state armed groups using child soldiers in 14 countries, all in the Global South. To date, there has been minimal research on the intersection of child soldiering and disability, or on challenges faced by disabled ex-combatants in such conflicts. We explore the current knowledge on this topic, avenues through which the rights of disabled people in post-conflict settings can be realised, and the importance of disability studies to praxis on child soldiers.